Latihan Peregangan Dinamis Dan Istirahat Aktif Menurunkan Keluhan Muskuloskeletal Pada Pekerja Di Industri Garmen - Syavira Nooryana; I Putu Gede Adiatmika; Susy Purnawati (Program Studi Magister Ergonomi Fisiologi Kerja Pascasarjana Universitas Udayana Denpasar Bekerjasama dengan Perhimpunan Ergonomi Indonesia (PEI), 2020)
Ergonomics problems experienced by workers at quality control and screen printing department at Adhi Fashion garment industry are the use of muscle power, work posture, and work time that still not in accordance to ergonomic principle. The workers carry out static and monotonous work for a long time and got 60 minutes pause per day for 6 working days. They were observed often take disguised pause while doing their jobs. They had musculoskeletal disorder with moderate to high scale complaints and low to moderate workload. There are exercises they can do by applicating of dynamic stretching exercise and active rest that can affect whole body muscles as an efforts to improve work posture and minimize taking of disguised pause. This study used treatment by subject design. The number of samples were 13 respondents consist of 8 workers from the quality control and 5 workers from the screen printing. At Period 1 the subject was working without intervention and Period 2 was working with intervention by applicating dynamic stretching exercise and active rest. The musculoskeletal disorder measured by the Nordic Body Map on Period 1 and Period 2. The normality of the data are tested using the Shapiro-Wilk Test. The intervention effect are tested using Paired-Sample T Test and Wilcoxon Sigend-Rank Test. Dynamic stretching exercise and active rest significantly affected to musculoskeletal complaints (p<0.05). There were reduction of musculoskeletal disorder (7.72%). Dynamic stretching exercise and active rest reduced of musculoskeletal disorder of workers at the quality control and screen printing in Adhi Fashion garment industry.